KONSEP CHECKS AND BALANCES SEBAGAI MANIFESTASI NEGARA HUKUM DALAM STRUKRUT KELEMBAGAAN NEGARA INDONESIA - Serli Tresia Lebrina; Karmelita Elu (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The principle of checks and balances is a fundamental instrument in modern constitutional democracies to ensure that power does not become concentrated in a single branch of government. In the Indonesian context, this principle gained clearer constitutional grounding after the Amendments to the 1945 Constitution of the Republic of Indonesia, which significantly reconstructed the state institutional framework. These amendments not only transformed the configuration of state organs but also introduced more balanced mechanisms of mutual control among the executive, legislative, and judicial branches. This study aims to provide an in-depth analysis of the concept of checks and balances as an integral aspect of constitutionalism in the Indonesian rule of law system, as well as its implementation in the interactions among state institutions. Employing a normative juridical methodology with statutory, conceptual, historical, and case approaches—including an examination of the decisions of the Constitutional Court—this research reveals that despite the relatively comprehensive adoption of mutual oversight mechanisms in the post-amendment constitutional design, various challenges persist. These include executive dominance, weak institutional counterweights, and inconsistent compliance with Constitutional Court rulings. The study affirms that the effectiveness of checks and balances depends not only on the institutional constitutional design but also on the strengthening of constitutional culture, judicial independence, and political accountability.